Detecting multiple associations in genome-wide studies - Dudbridge, Frank (Henry Stewart Talks, 2007)
Multiplicity, Combining evidence, False discovery rate, Q-value and local FDR, False positive report probability, Permutation testing
Archived at 2021/02/25